Tensile Characteristics of Carbon Fiber-Textile Reinforced Mortar with Aluminum Oxide Treated Anchorage Surfaces. (2nd September 2020) - Dinh, Ngoc Hieu; Park, Sung-Ho; Choi, Kyoung-Kyu
Abstract : The present study investigated the tensile characteristics of carbon fiber textile-reinforced mortar (TRM) with aluminum oxide treated anchorage surfaces. The main test parameters of this study include the thickness of TRM, the volume fraction of carbon fiber mesh, and the content of impregnated epoxy resin adopted in anchorage zones. The experimental results indicated that the tensile characteristics of TRM specimens in the pre-cracking stage are dominated by the mechanism of the mortar matrix; meanwhile, the tensile characteristics of TRM specimens in the cracked stage are governed by the volume fraction of carbon fiber mesh, and the amount of epoxy resin used in the anchorage zones. Based on the test results and material properties, an idealized bilinear model for predicting the tensile force–strain curve of TRM test specimens with aluminum oxide treated anchorage surfaces was developed based on ACI 549.4 R-13, and its prediction showed reasonable agreement with the test results.